OP95 Disability, work and welfare: individual and area-level influences on entering employment from health-related inactivity in the UK Labour Force Survey. (2nd September 2014) - Curnock, E; Popham, F; Leyland, A
Abstract : Background: Recent UK welfare reforms have sought to decrease the number of people out of work and claiming sickness benefits. As well as changing the assessment of entitlement, the reforms have introduced changes aimed at moving people back into the labour market. However, there is little understanding of the factors associated with transitions into employment from health-related labour market inactivity. The aim of this study was to investigate individual and area-level influences on transitions from health-related inactivity to employment and compare them with those leaving unemployment. Methods: We used data on working-age adults within the UK Labour Force Survey, who had been followed up longitudinally over five-quarters (Q1–5), merging 57 datasets covering the period 1998 to 2013. Individuals were categorised in terms of their labour market status at Q1 and Q5 (Q1 health-inactivity group n = 29, 130; Q1 unemployed group n = 14, 873). Multilevel logistic regression models were constructed with employment at Q5 as the main outcome measure. Separate models were run to investigate the influence of local labour market conditions, welfare claimant status, length of time since last employment, and job seeking activity, adjusting each model for relevant confounders. Results: Only 3.6% of the Q1 health-related inactivity group had entered employment at Q5, compared with 42.1% of the Q1 unemployed group. Higher local employment rates were associated with increased transitions to employment, both for the health-related inactivity group (OR 1.07 per 1% increase in employment; 95% CI 1.05 to 1.10) and those transitioning from unemployment (OR 1.08; 1.07 to 1.10), and fully accounted for all observed area-level variability. Sickness benefit claimant status had no significant association with employment transition for the health-related inactivity group (OR 1.10; 0.97 to 1.26); within the unemployed group higher odds of entering employment were observed for those not claiming unemployment benefit (OR 1.39; 1.29 to 1.49). Decreased length of time since last job and job seeking behaviour were each associated with increased rates of employment transition in both groups, but had greater influence in the health-related inactivity group than the unemployed. Conclusion: Transitions from health-related labour market inactivity into employment are rare events, and regional differences can be explained by local labour market conditions. Individual labour market attachment is important for the health-related inactivity group, but welfare claimant status is not a significant factor. These findings have direct relevance to policies aimed at increasing the rate of return to employment for those out of the labour market due to sickness and disability.